Cross‐Linked Spirocyclic Quaternary Ammonium‐Based Anion Exchange Membrane with Tunable Properties for Fuel Cell Applications. Issue 18 (13th May 2019) - Chu, Fuqiang; Chu, Xufeng; Zhang, Shuai; Zhu, Huanhuan; Ren, Yurong; Han, Juanjuan; Xie, Ruigang; Lin, Bencai; Ding, Jianning
Abstract: The alkaline stability of anion exchange membranes (AEMs) is crucial to the performance of alkaline anion exchange membrane fuel cells (AEMFCs). Here, we have prepared and characterization of a series of new spirocyclic quaternary ammonium‐based AEMs with good alkaline stability. The AEMs was obtained by UV‐initiated polymerization of N, N‐diallylpiperidinium bromide ([DAPip][Br]), styrene and acrylonitrile. The water uptake, swelling ratio, IEC and conductivity of the AEMs increase with increasing the [DAPip][Br] content. The transparent and mechanically robust AEMs show high conductivities (7.99×10 −2 S cm −1 at 80 °C) and good alkaline stability in 1 M KOH solution at 80 °C. The single cell with [DAPip][OH]20 showed a maximum power density of 93.9 mW cm −2 . The spirocyclic quaternary ammonium‐based AEMs with an aliphatic backbone will open up new prospects for the preparation of AEMs with excellent alkaline stability and high conductivity. Abstract : The spirocyclic quaternary ammonium‐based AEMs with an aliphatic backbone exhibit high alkaline stability, which will open up new prospects for the preparation of AEMs with excellent alkaline stability and high conductivity.